PEMBUATAN DAN KARAKTERISASI ELEKTRODA KARBON AKTIF DARI BIOMASSA PELEPAH AREN DENGAN PERSENTASE KOH - Haliza Putri; Rakhmawati Farma (Universitas Riau, 2021)
Energy is one of the basic needs in the human life cycle. Energy sources that are often used are non-recyclable energy sources, so a new innovation is needed in overcoming the energy crisis problem by using renewable natural materials, one of which is efforts to make energy storage components made from activated carbon.Activated carbon is a type of carbon that has a large surface area. Activated carbon can be applied as an activated carbon electrode such as lithium ion batteries and supercapacitor. Electrode in this study were produced from sugar palm midrib biomass. The electrodes production utilized chemical activation using Kalium Hydroxyde with various percentage of 5%, 10%, and 15% which of PA-05, PA-10, and PA-15 recpectively. Aktivated carbon electrodes were prepared through a pre-carbonization, chemical activation, carbonization process using N2 gas at temperature 600 °C and followed by physical activation using CO2 gas at temperature 900 °C. Analysis using XRD for microstructure show semicrystalline structure for the activated carbon electrodes which is by the presence of peaks at angel of 2θ around 24° and 44° with respectively crystal orientation (002) and (100).